2015
DOI: 10.1111/aec.12305
|View full text |Cite
|
Sign up to set email alerts
|

Seed survival of the tropical treeCryptocarya aschersoniana(Lauraceae): Consequences of habitat disturbance

Abstract: Seed survival in soil could be strongly influenced by habitat characteristics, but little is known about the behaviour of seeds sensitive to desiccation in seed banks installed in natural or disturbed habitats. Cryptocarya aschersoniana seeds disperse at the end of the rainy season but do not germinate immediately; thus, they may form seed banks in soil. This study evaluated the behaviour of C. aschersoniana seed banks induced in the natural environment of the species and in a disturbed area. Recently harveste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…A study in the same area as this research with desiccation-sensitive C. aschersoniana Mez. seeds, demonstrated that the formation of a transient seed bank is related to the preservation of the natural habitat of the species (Tonetti et al 2015). Similar behavior was observed in this study, implying that anthropization, (the adaption of an environment to meet human needs), negatively affects the establishment of species that produce desiccation-sensitive seeds.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A study in the same area as this research with desiccation-sensitive C. aschersoniana Mez. seeds, demonstrated that the formation of a transient seed bank is related to the preservation of the natural habitat of the species (Tonetti et al 2015). Similar behavior was observed in this study, implying that anthropization, (the adaption of an environment to meet human needs), negatively affects the establishment of species that produce desiccation-sensitive seeds.…”
Section: Discussionsupporting
confidence: 83%
“…The state of habitat conservation appears to be relevant for seed persistence in the soil. Cryptocarya aschersoniana Mez, a species from the Brazilian Atlantic Forest, produces recalcitrant seeds that form a transient seed bank; however, disturbed environments are unfavorable to the germination and regeneration of the species (Tonetti et al 2015).…”
Section: Introductionmentioning
confidence: 99%